Історія ліцензованої діяльності у сфері паливно-енергетичного комплексу України з давнини до початку XX ст - Піцикевич, В.; Pitsykevych, V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено історію ліцензованої діяльності у сфері паливно-енергетичного комплексу України з моменту зародження її витоків до початку XX століття. Встановлено, що витоки формування ліцензованої діяльності у сфері паливно-енергетичного комплексу України прослідковуються від Давньоруської держави. Найбільшого розвитку та нормативного врегулювання ліцензована діяльність у сфері ПЕК України набула за часів Австрії та Австро-Угорщини. This article examines the history of the licensed activity in the fuel and energy complex in Ukraine since the inception of its origins to the beginning of XX century. Based on the analysis of scientific publications and historical and legal sources it was determined that licensed activity in the fuel and energy complex in Ukraine developed long ago and therefore has a certain history. It was conducted a study about establishment of obligation for receiving by persons in government authorities, special permits for mining – berg regal – made it possible to conclude that essentially, berg regal was a special permit (license). It was established that berg regal was also distributed in Kyiv Rus’, thus forming the origins of the licensed activity in the fuel and energy complex in Ukraine traces from Ancient Rus’. Subsequently, during the stay of Ukraine under the Poland Kingdom, Rzecz Pospolita, Austria, Austria-Hungary, Moscow principality, Russian Empire licensed activities in the relevant area continue through evolution and has a constant development.
History of licensed activity in the fuel and energy complex in Ukraine from ancient times to the beginning of XX century
Keywords: регалія; гірнича регалія; ліцензія; ліцензована діяльність; паливно-енергетичний комплекс України; regal; berg regal; licence; licensed activity; fuel and energy complex in Ukraine